Dialektika Turats dan Nalar Kritis: Reorientasi Forum Diskusi Santri dalam Dekonstruksi Kitab Kuning di Pondok Pesantren Nurul Ilmi Wal Fikri Cukir Jombang - Sulton Sulton; Khoirotul Idawati; Jasminto Jasminto; Asriana Kibtiyah; Hanifudin Hanifudin (CV. Global Cendekia Inti, 2026)
This research examines the pivotal role of student discussion forums (syawir/bahtsul masail) in sharpening reasoning and analytical skills toward classical Islamic texts (Kitab Kuning) at Pondok Pesantren Nurul Ilmi Wal Fikri, Jombang. In an era dominated by instant digital information, the tradition of slow reading and deep textual analysis in pesantrens faces significant challenges. This study employs a descriptive qualitative approach with data collected through observation, in-depth interviews, and documentation. The findings indicate that discussion forums serve as a cognitive laboratory where students transform from passive recipients of knowledge into active analytical thinkers. Through the dialectic of logical reasoning (mantiq) and legal hermeneutics (ushul fikh), students develop the ability to deconstruct complex syntactic structures and reconstruct contextual meanings. Despite obstacles such as limited contemporary references and time constraints, these forums effectively cultivate an intellectual culture based on Ahlussunnah wal Jamaah principles, particularly tawasuth (moderation) and tawazun (balance). This research suggests that strengthening such deliberative methods is essential for maintaining the relevance of pesantren education in the 21st century.